(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Solid materials in the waste flow pattern rejected by the original user are solid wastes. If not processed, treated and disposed its impact on human health and environment are devastating. In municipalities of Kerala how waste is collected and treated and what is the range of their waste collection services is the subject matter of this study. The study tries to throw some light into the three major aspects, segregation, participation and use of modern methods which determine the quality of waste collection services. It reveals that out of the nine municipalities selected Palakkad is leading in segregation, Koyilandi in participation and Kottayam in use of modern methods.